2011
DOI: 10.1103/physrevb.83.165121
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure trends in the Srn+1RunO

Abstract: The identification of electronic states and the analysis of their evolution with n is key to understanding n-layered ruthenates. To this end, we combine polarization-dependent O 1s x-ray absorption spectroscopy, high-purity Sr n+1 Ru n O 3n+1 (n = 1,2,3) single crystals, and ab initio and many-body calculations. We find that the energy splitting between the empty x 2 − y 2 and 3z 2 − 1 state is considerably smaller than previously suggested and that, remarkably, Sr bands are essential to understanding the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 43 publications
7
40
0
Order By: Relevance
“…1 and 2, x-ray absorption spectra recorded on Ca 2 RuO 4 and Sr 2 RuO 4 are shown for different light polarizations and incident angles θ . Good agreement with previous XAS work [17,18] is found whenever overlap in temperature, polarization, and incident angle is present. As generally observed on cuprates [28], iridates [23], and ruthenates [17,18], the t 2g and e g states can be probed through oxygen hybridization on both the apical and planar oxygen sites, which have slightly different absorption resonance energies [28].…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…1 and 2, x-ray absorption spectra recorded on Ca 2 RuO 4 and Sr 2 RuO 4 are shown for different light polarizations and incident angles θ . Good agreement with previous XAS work [17,18] is found whenever overlap in temperature, polarization, and incident angle is present. As generally observed on cuprates [28], iridates [23], and ruthenates [17,18], the t 2g and e g states can be probed through oxygen hybridization on both the apical and planar oxygen sites, which have slightly different absorption resonance energies [28].…”
Section: Resultssupporting
confidence: 79%
“…The first two features in Figs to Ru t 2g hybridization with apical and planar oxygen, respectively [17,18]. Features at higher energies are attributed to hybridization with e g (d 3z 2 −r 2 and d x 2 −y 2 ) Ru orbitals [17].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…There is in fact no doubt that the stabilization of metamagnetism in the framework of the multiorbital character of the Ru bands is coupled with the lattice distortions as well as the evolution of the lattice parameters with both temperature and pressure. The in-plane rotations of the octahedra described above affect the site-specific local DOS and bandwidth in a different way [40], as predicted by ab initio calculations based on the local density approximation (LDA) [41]. In this paper it was reported that both the Ru t 2g crystal-field splitting = E zx/yz − E xy (and, as a consequence, the total orbital polarization calculated from LDA) is positive in the inner layer and negative in the two outer ones.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 shows the t 2g -like QP band structure of Sr 2 RuO 4 from the extended-LDA treatment. One observes the expected combined main features already known from the existing separate SOC 28,30,32 and correlated 26,29,31,47 studies, namely the lifting of degeneracies, e.g., close to the point for the bands with dominant xz,yz character, also resulting in now avoided band crossings, e.g., close to the X point, when including SOC. Electronic correlations lead in the present approximation to band-narrowing and -shifting.…”
Section: Correlated Electronic Structure Of the N=12 Compoundsmentioning
confidence: 77%